(untitled) (Raparin Journal of Humanities (RJH), 2025)
Indefiniteness is a linguistic phenomenon that exists in most languages of the world and it`s generally used in the Kurdish language well. It consists of not specifying some or all aspects of the speaker`s statement for various purposes. The purposes of this research are to gain better and more detailed knowledge and understanding of the role of indefiniteness in the Kurdish language, as well as identifying those structure and expressions that have the ability to express the meaning of indefiniteness in Kurdish. Much emphasis has been placed on indefiniteness as a syntactic process in the Kurdish language, but in reality, this process also exists at the morphological level. At the morphological level indefiniteness is expressed through independent morphemes such as pronouns, demonstratives, adjectives, adverbs, and indefinite verbs. The research has been conducted according to the descriptive analysis method, and the representative material has been from middle Kurdish. The problem this research investigates is that in Kurdish linguistics, indefiniteness has only been associated with verbs while other parts of speech have not been discussed. The research aims to identify all words that carry the concept of indefiniteness and has concluded that nouns, pronouns, and adjectives as parts of speech and independent words carry concepts of indefiniteness. Part of this concept is conveyed either through the meaning of the word itself or through the addition of affixes and clitics. The use of each of these word classes, whether intentionally or unintentionally, conveys this concept.